KLASIFIKASI EMOSI TOKOH QAIS AL-QARANI DALAM NOVEL LAYLA MAJNUN KARYA NIZAMI AL-GANJAVI: KAJIAN PERSPEKTIF DAVID KRECH - Hamzah, Imam; Rusdiawan, Rusdiawan; Mahyudi, Johan (Jurnal Ilmiah Mandala Education (JIME), 2022)
The problem in this research is how to classify the emotions of the character Qais Al-Qarani in the novel Layla Majnun by Nizami Al-Ganjavi based on the study of David Krech's perspective. This study aims to determine the emotional classification of the character Qais Al-Qarani in the novel Layla Majnun by Nizami Al-Ganjavi based on the study of David Krech's perspective. The theory used in this research is David Krech's classification of emotions. This research is qualitative. The data source in this study is the novel Layla Majnun by Nizami Al-Ganjavi. The data collection method used is the library method and documentation. Based on the results of data analysis conducted on the novel Layla Majnun, it can be concluded that the character Qais Al-Qarani in the novel Layla Majnun has seven classifications of emotions based on David Krech's perspective. From the results of data analysis in this study, it can be seen that various classifications of Qais Al-Qarani's emotions are as diverse as the concept of guilt experienced by Qais is illustrated when he makes a love rope which according to people is not good so that he separates from Layla. The pent-up guilt experienced by Qais is seen when a mother tries to persuade him to go home but Qais has no desire to go home. Self-punishment was seen when Qais hurt himself by writhing on a thorn and hitting his head. He did this to relieve the tension he felt. The shame that Qais experienced was seen when he had a guest who came from far away. The person's name is Salam. Salam wanted to accompany Qais to his Majnun but Qais refused because he felt he would not be able to share anything with Salam. He was just an isolated madman. The sadness that was felt by Qais himself was seen when his separation from his lover Layla occurred. The separation made him feel great sadness. Longing for her lover has brought so much suffering, tears, pain, and all forms of suffering and misfortune. The hatred that Qais felt was seen when he left the lives of those who were close to him and chose to live in the desert and wander. He feels that his environment never understands and accepts the reason why he acts like a crazy person. The love experienced by Qais is seen when he prays and asks God to end his life and death picks him up. He did this because the lover he loved so much had died.